PROBLEMATIK PEMBELAJARAN MAHASISWA BERKEBUTUHAN KHUSUS PADA PERGURUAN TINGGI INKLUSIF - Muhammad Azimi; Ali Rachman; Mirnawati Mirnawati (FKIP ULM, 2020)
One form of handling needed by children with special needs is educational services. Inclusive education is a system that complements the previous ABK education system. However, the implementation of inclusive education in higher education has just taken place, namely in 2017. Since that year, Lambung Mangkurat University has also organized inclusive education. Several previous studies have shown that learning in inclusive education in Indonesia still has problems. This study intends to reveal the problems with the learning of students with special needs in the Special Education Study Program, Faculty of Teacher Training and Education, Lambung Mangkurat University. This study uses a qualitative research approach. The data sources in this study amounted to 23 people, which were divided into five students with special needs in the Special Education Study Program, ten volunteers accompanying MBK from the Disability Service Unit, and eight lecturers from the Special Education Study Program. Data collection techniques in this study were used to interview and documentation techniques. Analysis of the data used in this study is the analysis model of Miles and Huberman. This study describes that there are still various problems in the learning of students with special needs. The problem with planning is that the MBK assessment carried out so far is not comprehensive, and the RPS for students with special needs is not modified. At the implementation stage, problems that arise, namely the implementation of MBK learning is not following the prepared RPS, MBK is learning that is not modified, another problem is the ability of the MBK companion volunteer that is not optimal, MBK is learning that does not apply inclusive settings, and learning media are still not fully available. At the evaluation stage, there are problems, including the evaluation of MBK learning that is not modified and the evaluation of MBK learning that is still not running.Keywords: Higher education; MBK learning; Problematic Salah satu bentuk penangan yang dibutuhkan oleh anak berkebutuhan khusus adalah layanan pendidikan. Pendidikan inklusif merupakan suatu sistem penyempurna dari sistem pendidikan ABK sebelumnya. Namun, penyelenggaraan pendidikan inklusif di perguruan tinggi baru-baru saja berlangsung, yaitu tahun 2017. Sejak tahun itu pula, Universitas Lambung Mangkurat turut menyelenggarakan pendidikan inklusif. Beberapa penelitian sebelumnya menunjukkan bahwa pembelajaran dalam pendidikan inklusif di Indonesia masih memiliki permasalahan. Penelitian ini bermaksud mengungkap apa saja problematik pada pembelajaran mahasiswa berkebutuhan khusus di Program Studi Pendidikan Khusus, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat. Penelitian ini menggunakan pendekatan penelitian1kualitatif. Sumber data dalam penelitian ini berjumlah 23 orang yang terbagi menjadi 5 orang mahasiswa berkebutuhan1khusus Prodi Pendidikan Khusus, 10 orang volunter pendamping MBK dari Unit Layanan Disabilitas, dan 8 orang dosen Prodi Pendidikan Khusus. Teknik pengumpulan data pada penelitian ini menggunakan teknik wawancara dan dokumentasi. Analisis data yang digunakan dalam penelitian ini adalah model analisis Miles dan Huberman. Hasil penelitian ini mendeskripsikan bahwa masih terdapat berbagai problematik dalam pembelajaran mahasiswa berkebutuhan khusus. Problematik pada perencanaan, yaitu asesmen MBK yang dilaksanakan selama ini tidak komprehensif dan RPS mahasiswa berkebutuhan khusus yang tidak dimodifikasi. Pada tahap pelaksanaan, problematik yang muncul, yaitu pelaksanaan pembelajaran MBK tidak sesuai dengan RPS yang disusun, ada pembelajaran MBK yang tidak dimodifikasi, problematik lainnya adalah kemampuan volunter pendamping MBK yang belum optimal, ada pembelajaran MBK yang tidak menerapkan setting inklusif, serta media pembelajaran masih belum tersedia secara lengkap. Pada tahap evaluasi, terdapat problematik, di antaranya evaluasi pembelajaran MBK yang tidak dimodifikasi dan evaluasi pembelajaran MBK masih belum berjalan dengan semestinya.Kata Kunci: Problematik; Pembelajaran MBK; Perguruan tinggi